Karakteristik dan Pendekatan Aspek Sosial Hukum Islam - Mudassir Mudassir; Edi Gunawan (IAIN Manado, 2017)
This article is a conceptual study of the characteristics and approaches of social aspects of Islamic law. This study is important because Islamic law encompasses various dimensions, namely the abstract dimension, in the form of all the commandments and the prohibitions of Allah and His Messenger, and the concrete dimension, in the form of behavior that is steady among Muslims as an effort to do the command of Allah and His Messenger, In addition, Islamic law also includes substances that are internalized into various social institutions. Therefore, the study of the social aspects approaches in Islamic law is very important. Islamic law has a character, namely rabbaniyah, syumul, al-wasthiyah, and insanity. There are several methods of Islamic law enforcement conducted by aspects of the social approach, especially in Indonesia, namely the establishment of Islamic law through fiqh, the establishment of Islamic law through the law, the establishment of Islamic law through jurisprudence, and the affirmation of Islamic law through fatwas.